Nucleon thermal width owing to pion-baryon loops and its contributions to shear viscosity - Ghosh, Sabyasachi [UNESP] (American Physical Society (APS), 2014)
In real-time thermal field theory, the standard expression of shear viscosity for nucleonic constituents is derived from the two-point function of nucleonic viscous stress tensors at finite temperature and density. The finite thermal width or Landau damping is traditionally included in the nucleon propagators. This thermal width is calculated from the in-medium self-energy of nucleons for different possible pion-baryon loops. The dynamical part of nucleon-pion-baryon interactions are accounted for by the effective Lagrangian densities of standard hadronic model. The shear viscosity to entropy density ratio of the nucleonic component decreases with the temperature and increases with the nucleon chemical potential. However, adding the contribution of the pionic component, the total viscosity to entropy density ratio also reduces with the nucleon chemical potential when the mixing effect between pion and nucleon components in the mixed gas is considered. Within the hadronic domain, the viscosity to entropy density ratio of the nuclear matter gradually reduces as temperature and nucleon chemical potential increase and therefore the nuclear matter is approaching the (nearly) perfect-fluid state. © 2014 American Physical Society.